Vous êtes sur la page 1sur 1

0 𝜋 𝜋 𝜋 𝜋 𝜋

6 4 3 2
sin 0 1 √2 √3 1 0
(x) 2 2 2
cos 1 √3 √2 1 0 -1
(x) 2 2 2

sin(𝑎 + 𝑏) = 𝑠𝑖𝑛𝑎𝑐𝑜𝑠𝑏 + 𝑠𝑖𝑛𝑏𝑐𝑜𝑠𝑎 cos(𝑎 + 𝑏) = 𝑐𝑜𝑠𝑎𝑐𝑜𝑠𝑏 − 𝑠𝑖𝑛𝑎𝑠𝑖𝑛𝑏


sin(𝑎 − 𝑏) = 𝑠𝑖𝑛𝑎𝑐𝑜𝑠𝑏 − 𝑠𝑖𝑛𝑏𝑐𝑜𝑠𝑎 cos(𝑎 − 𝑏) = 𝑐𝑜𝑠𝑎𝑐𝑜𝑠𝑏 + 𝑠𝑖𝑛𝑎𝑠𝑖𝑛𝑏
𝑎+𝑏 𝑎−𝑏 𝑎+𝑏 𝑎−𝑏
𝑠𝑖𝑛𝑎 + 𝑠𝑖𝑛𝑏 = 2𝑠𝑖𝑛 𝑐𝑜𝑠 𝑐𝑜𝑠𝑎 + 𝑐𝑜𝑠𝑏 = 2𝑐𝑜𝑠 𝑐𝑜𝑠
2 2 2 2
𝑎−𝑏 𝑎+𝑏 𝑎+𝑏 𝑎−𝑏
𝑠𝑖𝑛𝑎 − 𝑠𝑖𝑛𝑏 = 2𝑠𝑖𝑛 𝑐𝑜𝑠 𝑐𝑜𝑠𝑎 − 𝑐𝑜𝑠𝑏 = −2𝑠𝑖𝑛 𝑠𝑖𝑛
2 2 2 2
− cos(𝑎 + 𝑏) + cos⁡(𝑎 − 𝑏) cos(𝑎 + 𝑏) + cos⁡(𝑎 − 𝑏)
𝑠𝑖𝑛𝑎 ∙ 𝑠𝑖𝑛𝑏 = 𝑐𝑜𝑠𝑎 ∙ 𝑐𝑜𝑠𝑏 =
2 2
sin(𝑎 + 𝑏) + sin⁡(𝑎 − 𝑏) sin(𝑎 + 𝑏) + sin⁡(𝑎 − 𝑏)
𝑠𝑖𝑛𝑎 ∙ 𝑐𝑜𝑠𝑏 = 𝑠𝑖𝑛𝑎 ∙ 𝑐𝑜𝑠𝑏 =
2 2
𝑠𝑖𝑛2𝑥 = 2𝑠𝑖𝑛𝑥 ∙ 𝑐𝑜𝑠𝑥 𝑐𝑜𝑠2𝑥 = 𝑐𝑜𝑠 𝑥 − 𝑠𝑖𝑛2 𝑥
2

𝑠𝑖𝑛2 𝑥 + 𝑐𝑜𝑠 2 𝑥 = 1 𝑐𝑜𝑠2𝑥 = 2𝑐𝑜𝑠 2 𝑥 − 1


𝑐𝑜𝑠2𝑥 = −2𝑠𝑖𝑛2 𝑥 + 1
1 − 𝑐𝑜𝑠2𝑥 1 + 𝑐𝑜𝑠2𝑥
|𝑠𝑖𝑛𝑥| = √ |𝑐𝑜𝑠𝑥| = √
2 2

2
𝑡𝑔2 𝑥 1 2
1 𝑐𝑡𝑔2 𝑥
𝑠𝑖𝑛 𝑥 = = 𝑐𝑜𝑠 𝑥 = =
1 + 𝑡𝑔 𝑥 1 + 𝑐𝑡𝑔2 𝑥
2 1 + 𝑡𝑔2 𝑥 1 + 𝑐𝑡𝑔2 𝑥
𝑥 𝑥
2𝑡𝑔 1 − 𝑡𝑔2
𝑠𝑖𝑛𝑥 = 2 𝑐𝑜𝑠𝑥 = 2
𝑥 𝑥
1 + 𝑡𝑔2 1 + 𝑡𝑔2
2 2
𝑡𝑔𝑎 + 𝑡𝑔𝑏 𝑐𝑡𝑔𝑎 ∙ 𝑐𝑡𝑔𝑏 − 1
𝑡𝑔(𝑎 + 𝑏) = 𝑐𝑡𝑔(𝑎 + 𝑏) =
1 − 𝑡𝑔𝑎 ∙ 𝑡𝑔𝑏 𝑐𝑡𝑔𝑏 + 𝑐𝑡𝑔𝑎
𝑡𝑔𝑎 − 𝑡𝑔𝑏 𝑐𝑡𝑔𝑎 ∙ 𝑐𝑡𝑔𝑏 + 1
𝑡𝑔(𝑎 − 𝑏) = 𝑐𝑡𝑔(𝑎 − 𝑏) =
1 + 𝑡𝑔𝑎 ∙ 𝑡𝑔𝑏 𝑐𝑡𝑔𝑏 − 𝑐𝑡𝑔𝑎
sin⁡(𝑎 ± 𝑏) sin⁡(𝑏 ± 𝑎)
𝑡𝑔𝑎 ± 𝑡𝑔𝑏 = 𝑐𝑡𝑔(𝑎 ± 𝑏) =
𝑐𝑜𝑠𝑎 ∙ 𝑐𝑜𝑠𝑏 𝑠𝑖𝑛𝑎 ∙ 𝑠𝑖𝑛𝑏
2
2
𝑠𝑖𝑛 𝑥 1 − 𝑐𝑜𝑠 2 𝑥 1 2
2
𝑐𝑜𝑠 𝑥 1 − 𝑠𝑖𝑛2 𝑥 1
𝑡𝑔 𝑥 = = = 𝑐𝑡𝑔 𝑥 = = =
1 − 𝑠𝑖𝑛2 𝑥 𝑐𝑜𝑠 2 𝑥 𝑐𝑡𝑔2 𝑥 1 − 𝑐𝑜𝑠 2 𝑥 𝑠𝑖𝑛2 𝑥 𝑡𝑔2 𝑥

FUNCȚIA sinx cosx


Existența 𝑠𝑖𝑛𝑥 ∈ [−1,1] 𝑐𝑜𝑠𝑥 ∈ [−1,1]
Paritate sin(−𝑥) = −𝑠𝑖𝑛𝑥 cos(−𝑥) = 𝑐𝑜𝑠𝑥
Reduceri sin(𝜋 − 𝑥) = 𝑠𝑖𝑛𝑥 cos(𝜋 − 𝑥) = −𝑐𝑜𝑠𝑥
sin(𝜋 + 𝑥) = −𝑠𝑖𝑛𝑥 cos(𝜋 + 𝑥) = −𝑐𝑜𝑠𝑥
sin(2𝜋 − 𝑥) = −𝑠𝑖𝑛𝑥 cos(2𝜋 − 𝑥) = 𝑐𝑜𝑠𝑥

Vous aimerez peut-être aussi